2017
DOI: 10.1021/acs.nanolett.7b00627
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of the Band Gap Transition in Atomically Thin ReS2

Abstract: ReS is considered as a promising candidate for novel electronic and sensor applications. The low crystal symmetry of this van der Waals compound leads to a highly anisotropic optical, vibrational, and transport behavior. However, the details of the electronic band structure of this fascinating material are still largely unexplored. We present a momentum-resolved study of the electronic structure of monolayer, bilayer, and bulk ReS using k-space photoemission microscopy in combination with first-principles calc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
90
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(102 citation statements)
references
References 41 publications
10
90
2
Order By: Relevance
“…While finalizing our work, a paper appeared on arXiv that also reported a non-negligible out-of-plane dispersion of ReS 2 [49]. Their data seem to be consistent with ours.…”
Section: Discussionsupporting
confidence: 83%
“…While finalizing our work, a paper appeared on arXiv that also reported a non-negligible out-of-plane dispersion of ReS 2 [49]. Their data seem to be consistent with ours.…”
Section: Discussionsupporting
confidence: 83%
“…Note added. Recently, two more reports of ARPES studies of ReS 2 in bulk and thin-layer forms appeared on arXiv (both now published) which confirm the three-dimensional dispersion of the valence band structure [41] and, for the bulk material, indicate via Rb-doping that the band extrema are indeed located at Z, as proposed above [42].…”
Section: Discussionmentioning
confidence: 57%
“…From our first‐principle calculations with G 0 W 0 approximation (Figure S4, Supporting Information), we found that the bilayer AA stacking ReS 2 has a direct bandgap while bilayer AB stacking has an indirect bandgap. This suggests that the bilayer sample studied by Gehlmann et al [ 44 ] has AA stacking. Wang et al studied a 3L ReS 2 with Raman and PL.…”
Section: Figurementioning
confidence: 88%